2013
DOI: 10.1038/nature12668
|View full text |Cite
|
Sign up to set email alerts
|

Structural change in molten basalt at deep mantle conditions

Abstract: Silicate liquids play a key part at all stages of deep Earth evolution, ranging from core and crust formation billions of years ago to present-day volcanic activity. Quantitative models of these processes require knowledge of the structural changes and compression mechanisms that take place in liquid silicates at the high pressures and temperatures in the Earth's interior. However, obtaining such knowledge has long been impeded by the challenging nature of the experiments. In recent years, structural and densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
166
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(181 citation statements)
references
References 38 publications
14
166
1
Order By: Relevance
“…Although the effect of temperature requires further exploration to obtain better insight into melts, recent high-pressure radiative thermal conductivity measurements on Earth's deep minerals 11,32 and previous Mössbauer measurements on glasses/liquids 33,34 show that the effect of temperature on the optical properties of minerals and on the electronic configurations of glasses/liquids is fairly moderate, which suggests that the analogy in electronic configurations between glass and melt works well. Very recently, Sanloup et al 35 reported structural changes in molten basalt up to pressures of 60 GPa by means of in situ synchrotron X-ray diffraction, and they have successfully shown that changes in the Si-O coordination number of molten basalt are highly consistent with those observed in silica glass [36][37][38] , thereby providing experimental evidence in support of the validity of the analogy between silicate glasses and melts in atomic structure.…”
Section: Discussionmentioning
confidence: 84%
“…Although the effect of temperature requires further exploration to obtain better insight into melts, recent high-pressure radiative thermal conductivity measurements on Earth's deep minerals 11,32 and previous Mössbauer measurements on glasses/liquids 33,34 show that the effect of temperature on the optical properties of minerals and on the electronic configurations of glasses/liquids is fairly moderate, which suggests that the analogy in electronic configurations between glass and melt works well. Very recently, Sanloup et al 35 reported structural changes in molten basalt up to pressures of 60 GPa by means of in situ synchrotron X-ray diffraction, and they have successfully shown that changes in the Si-O coordination number of molten basalt are highly consistent with those observed in silica glass [36][37][38] , thereby providing experimental evidence in support of the validity of the analogy between silicate glasses and melts in atomic structure.…”
Section: Discussionmentioning
confidence: 84%
“…The results are therefore pertinent for understanding the properties of high-density liquids to aid, e.g., in the design of glasses with new network topologies (8,(38)(39)(40). They are also relevant to magma-related melts because the onset of higher coordinated modifying species changes the network polymerization (i.e., the ratio of bridging versus nonbridging oxygen atoms), thereby affecting the transport properties (e.g., viscosity) and compressibility (3)(4)(5)(6)(7).…”
Section: Discussionmentioning
confidence: 99%
“…In the pressure regime corresponding to the transformation from AO 3 to AO 4 polyhedra in the case of B 2 O 3 or from AO 4 to AO 6 polyhedra in the cases of SiO 2 and GeO 2 , a linear dependence for r O was assumed, a hypothesis that is supported by the available information (SI Text, section 1.5). This method for estimating r O was also applied to the data for molten basalt under deep mantle conditions (7).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, high-pressure density data are lacking due to experimental challenges. Although many experiments on both melts and glasses densities have been carried out in large volume apparatus to pressures of 20 GPa (12, 13), the few studies conducted in the diamond anvil cell (DAC) were limited to [50][51][52][53][54][55][56][57][58][59][60]15). Studying glasses is a potential alternative for understanding melts because many of their physical properties are similar to those of melt: from the atomistic scale, with the evolution of the silicon coordination number from fourfold to sixfold from 0 to 40 GPa (15), to the macroscopic scale with similarities in compressibility (16,17).…”
mentioning
confidence: 99%